Reorientasi Jurusan Manajemen Pendidikan Islam (MPI) antara Tenaga Kependidikan dan Tenaga Pendidik - Misbah, M. (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
This article discusses the problems faced by the majority of students MPI FTIK IAIN Purwokerto. On the one hand, there is the desire of MPI students to become educators, and on the other hand according to the Department, they are oriented to become educational personnel. The study focused on curriculum content and policy of MPI Department of FTIK IAIN Purwokerto. With the method of unstructured in-depth interview, documentation, moderate participant observation and data analysis, it is found that the orientation of MPI Department is based on the vision, the mission stated in the profession to be achieved that is the main profession and the alternative profession. To support the orientation of the Department of MPI, the scientific core of MPI in the curriculum of the Department which becomes its distinguishing character is related to the science MPI contained in the MPI 001 to MPI 025 course code. The way of Department in socializing the orientation of the Department as well as construct the orientation of students to fit the orientation of the Department is through Introduction Academic Orientation activities, provision of Academic Guidebook, Maximization of Role of PA, Prodi, HMPS / HMJ, MPI Department profile viewing on IAIN Purwokerto website.Â Ø¯Ø±Ø³ ÙØ°Ø§ Ø§ÙÙÙØ§Ù Ø§ÙÙØ´Ø§ÙÙ Ø§ÙØªÙ ÙÙØ§Ø¬ÙÙØ§ Ø·ÙØ§Ø¨ ÙØ³Ù Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØ¹ÙÙÙ Ø§ÙØªØ¹ÙÙÙÙØ© Ø¨Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ÙÙØ±ÙÙÙÙØ±ØªÙ. Ø«ÙØ© Ø¥Ø±Ø§Ø¯Ø© ÙÙ Ø·ÙØ§Ø¨ ÙØ°Ø§ Ø§ÙÙØ³Ù ÙØ£Ù ÙÙÙÙÙØ§ ÙØ¯Ø±ÙØ³ÙÙ Ø ÙÙÙ Ø¬Ø§ÙØ¨ Ø¢Ø®Ø±Â  Ø£Ù ÙÙÙÙÙØ§ ÙÙØ¸ÙÙÙÙ ØªØ±Ø¨ÙÙÙÙ. ØªÙØ±ÙØ²Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ ÙØØªÙÙ Ø§ÙÙÙÙØ¬ ÙÙØ±Ø§Ø±Ø§Øª ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØ¹ÙÙÙ Ø§ÙØªØ¹ÙÙÙÙØ© ÙÙ ÙØ°Ù Ø§ÙØ¬Ø§ÙØ¹Ø©. ØªØ¬ÙØ¹ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¹Ù Ø·Ø±ÙÙ Ø§ÙÙÙØ§Ø¨ÙØ© ØºÙØ± Ø§ÙØªØ±ÙÙØ¨ÙØ©Ø ÙØ§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙÙØªÙØ¨Ø©Ø ÙØ§ÙÙÙØ§ØØ¸Ø© Ø¨Ø´Ø¨Ù Ø§ÙÙØ´Ø§Ø±ÙØ©Ø ÙØ¨Ø¹Ø¯ Ø§ÙØªØÙÙÙ ØØµÙ Ø§ÙØ¨Ø§ØØ« Ø¹ÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« ÙÙ Ø£Ù Ø§ØªÙØ¬Ø§Ù ÙØ³Ù Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙØ§Ø³Ø¨ Ø¨Ø±Ø¤ÙØªÙ ÙØ±Ø³Ø§ÙØªÙ Ø§ÙÙØªÙØ«ÙÙØªØ§Ù ÙÙ Ø§ÙÙÙÙØ© Ø§ÙØªÙ ØØ§ÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙØØµÙÙ Ø¹ÙÙÙØ§Ø ÙÙ Ø§ÙÙÙÙØ© Ø§ÙØ£Ø³Ø§Ø³ÙØ© ÙØ§ÙÙÙÙØ© Ø§ÙØ§Ø®ØªÙØ§Ø±ÙØ©. ÙÙØ¯Ø¹Ù Ø§ØªØ¬Ø§Ù Ø§ÙÙØ³ÙØ ÙØ¥Ù ÙØ¦Ø© Ø§ÙØ¹ÙÙÙ ÙÙØ°Ø§ Ø§ÙÙØ³Ù ÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØªÙÙÙØ²Ù ÙÙ Ø§ÙØ¹ÙÙÙ Ø§ÙÙØªØ¹ÙÙØ© Ø¨Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙÙ ÙÙØªÙØ¨Ø© ÙÙ Ø±ÙÙØ² Ø§ÙÙÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© ÙÙ 001 MPI â 0025 MPI . ÙØ§ÙØ·Ø±ÙÙØ© Ø§ÙØªÙ Ø§ØªÙØ®Ø°ÙØ§ Ø§ÙÙØ³Ù ÙÙØªØ¹Ø±ÙÙ Ø¨ÙØ°Ø§ Ø§ÙØ§ØªØ¬Ø§Ù ÙÙÙ ÙÙØ³ Ø§ÙÙÙØª ØªÙÙÙÙ Ø§ØªØ¬Ø§Ù Ø§ÙØ·ÙØ§Ø¨ ÙÙÙÙÙ Ø§ØªØ¬Ø§ÙÙÙ ÙÙØ§Ø³Ø¨Ø§ Ø¨Ø§ØªØ¬Ø§Ù Ø§ÙÙØ³ÙØ ÙÙ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØªØ¹Ø±ÙÙ Ø§ÙØ£ÙØ§Ø¯ÙÙÙÙØ ØªÙØ²ÙØ¹ ÙØªØ§Ø¨ Ø§ÙØ¥Ø±Ø´Ø§Ø¯ Ø§ÙØ£ÙØ§Ø¯ÙÙÙØ ØªØ¹Ø²ÙØ² ÙØªÙÙÙØ© Ø¯ÙØ± Ø§ÙÙØ´Ø±Ù Ø§ÙØ£ÙØ§Ø¯ÙÙÙ ÙÙ ÙØ¨Ù Ø§ÙÙØØ§Ø¶Ø±ÙÙØ ÙØ§ÙÙØ³ÙØ ÙÙÙØ¸ÙÙØ§Øª Ø§ÙØ·ÙØ¨Ø© ÙÙ Ø§ÙÙØ³Ù ÙØ§ÙÙÙÙØ©Ø ÙØ§ÙØªØ¹Ø±ÙÙ Ø¨ÙØ³Ù Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø¹Ù Ø·Ø±ÙÙ Ø§ÙÙÙÙØ¹ ÙÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ÙÙØ±ÙÙÙÙØ±ØªÙ ÙÙ Ø§ÙØ§ÙØªØ±ÙØª